Smart spectral vision system - Tan, Ryan Kheng Hup (Nanyang Technological University, 2022)
Spectral imaging collects images in different bands or sub-bands of the electromagnetic spectrum to obtain extra information that human vision cannot capture. An image recognition system uses shapes for individual identification. The current image recognition system operates in the visible range of the electromagnetic spectrum. Current image recognition systems operate in the visible spectrum from 350nm to 740nm wavelengths. Nowadays, image recognition technology is easily seen as applicable in daily lives, from face recognition for security purposes to even tracking humans in public via CCTVs. Current image recognition technology mainly uses 2D images or 3D images to feed as data to train the neural network.